Controlled homeodynamic concept using a conformable calculus in artificial biological systems. (November 2020) - Ibrahim, Rabha W.; Altulea, Dania
Abstract: Homeodynamic system (HS) in the biological studies (from the Greek homoios (similar) and Dynamis (energy)) designates the accommodating instruments of stabilizing and repairing of the fundamental reliability and functional efficiency of living schemes. In this effort, we employ the concept of conformable calculus (CC) to generalize the homeodynamic system. The generalization requires a controller in the system to preserve the variables robustly regulated, oscillated, and synchronized variables at a certain set point. Here, we show how the selectivity of the CC makes differences in the behavior of an oscillation and the other properties of HS.